The Problem of Religious Toleration: Assessment Values in Surah Al-Kafirun - Muh. Syaifudin (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
inter-religious tolerance is an absolute case in this era of globalization. nevertheless, the limits of tolerance necessary to ensure a life of harmony, harmonious and peaceful. Even in the interaction between religious communities themselves. In general, historical figures, scholars, as well as religious teachings, all have the principles of tolerance. Hindu religion in India, Buddhist religion in Asia and Islam in Arab, although born and grown in certain areas, but all of them calling for tolerance. That is what causes these religions still exist in various parts of the world until now. Islam, in terms of tolerance has rules and clear boundaries. In the matter of faith, tolerance means respecting others without bothering. This is referred to in Sura Al-Kafirun. This surah illustrates that faith can not be replaced even though bought by anything in this world. Surah which consists of six ayat also asserts that the other party can not we forced to follow our beliefs. keywords :  Tolerance, religion, Al-Kafirun